Antecedents Purchase Intention Local Fragrance - Muhammad Ammar Farras; Ayu Ekasari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Local fragrance brands such as SAFF & Co, Mykonos, and HMNS have successfully built strong identities through signature products, influencer collaborations, and digital platforms. The Indonesian fragrance industry is showing a positive trend with more and more consumers recognizing the importance of fragrance. This research is to analyze social media marketing, brand awareness, consumer brand engagement on purchase intention of local fragrance. This research uses qualitative methods and uses purposive sampling techniques. Through a questionnaire as a data collection tool, a sample size of 200 respondents was obtained. The questionnaire was distributed to individual users of local fragrance brands such as SAFF & Co, Mykonos, and HMNS and also often see content about local fragrance products such as SAFF & Co, Mykonos, and HMNS using Google Form. Hypothesis testing using the structural equation model (SEM) method. The results of this study reveal that social media marketing, brand awareness, consumer brand engagement significantly affect purchase intention. Based on the results of the study, the managerial implications underscore the importance of improving integrated digital marketing strategies among managers of local perfume companies. This strategy includes developing user-generated content campaigns, building a memorable brand with consistent visuals, and creating emotional bonds through personal stories and active interactions. Awareness is crucial to ensure that local perfume marketing strategies are carried out in an effective way, thereby increasing purchase intention and contributing to the growth of Indonesia's local perfume industry.